2021
DOI: 10.1186/s12885-021-08995-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiotherapy combined with nimotuzumab vs. chemoradiotherapy for locally recurrent nasopharyngeal carcinoma

Abstract: Background The present study compared the effectiveness and toxicity of two treatment modalities, namely radiotherapy combined with nimotuzumab (N) and chemoradiotherapy (CRT) in patients with locally recurrent nasopharyngeal carcinoma (LR-NPC). Methods Patients with LR-NPC who were treated with radiotherapy were retrospectively enrolled from January 2015 to December 2018. The treatment included radiotherapy combined with N or platinum-based induct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Compared with chemotherapeutic agents, the use of targeted therapy and immunotherapy in recurrent NPC is relatively limited, and in most cases they are not used alone, but in combination with chemotherapeutic agents or radiotherapy to provide better benefits [ 115 , 116 , 117 , 118 , 119 ]. A clinical study published by Ng et al showed that weekly IMRT with docetaxel plus cetuximab was shown to be effective in advanced recurrent NPC compared to TPF-induced chemotherapy, with a 3-year progression-free survival rate of 35.7% [ 107 ].…”
Section: Treatment Of Recurrent Npcmentioning
confidence: 99%
“…Compared with chemotherapeutic agents, the use of targeted therapy and immunotherapy in recurrent NPC is relatively limited, and in most cases they are not used alone, but in combination with chemotherapeutic agents or radiotherapy to provide better benefits [ 115 , 116 , 117 , 118 , 119 ]. A clinical study published by Ng et al showed that weekly IMRT with docetaxel plus cetuximab was shown to be effective in advanced recurrent NPC compared to TPF-induced chemotherapy, with a 3-year progression-free survival rate of 35.7% [ 107 ].…”
Section: Treatment Of Recurrent Npcmentioning
confidence: 99%
“… 30 Previous studies reported that nearly 55% of rNPC patients exhibited late radiation injuries more severe than grade 3 injuries, whereas 30% exhibited grade 5 injuries including nasopharyngeal necrosis, necrosis of the internal carotid artery, or other vessels, temporal lobe necrosis, and so on. 15 , 31 Some of these severe toxicities may be related to the large fraction size used in previously heavily irradiated normal tissues. In the current study, all patients were initially treated with RT including conventional RT and IMRT.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 29 , 32 Zong et al reported that the rT category and chemotherapy are associated with the incidence of severe late radiation injury. 31 It was demonstrated that rNPC patients receiving RCT suffered more late toxicity than those treated with RT alone. 33 Previous studies have indicated that chemotherapy was the major contributor to severe grade 3 acute hematological toxicities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations